BIODIVERSITY OF HEMIPTERA (HETEROPTERA) OF THE INFRAORDER CIMICOMORPHA I IN THE ILE-ALATAU STATE NATIONAL NATURE PARK (SOUTH-EAST KAZAKHSTAN) (Experimental biology, 2022)
The article presents the results of field research conducted in 2020 on the territory of the Ile-Alatau State National Natural Park. As a result of the conducted research, 21 species belonging to 4 families of hemiptera of the infraorder Cimicomorpha I were identified. Among them, the predominant species composition of the family: Nabidae (7 species, 33%), Anthocoridae (7 species, 33%), Tingidae (5 species, 24%), and only 2 species (10%) are known from the Reduviidae family. According to trophic specialization, they are divided into zoophages (16 species), phytophages (4 species) and mycetophages (1 species). According to the number of generations per year, the hemiptera of the Ile-Alatau State National Nature Park are divided into 2 groups: monovoltine (19 species), polyvoltine (2 species). From an ecological point of view, the species in the research area are mesophilic species. Among the hemiptera of the Ile-Alatau SNNP, 16 species (76%) overwinter in the imago stage, 3 species (14%) in the imago and larval stages, and 2 species (7%) in the egg stage
Keywords: hemiptera, infraorder Cimicomorpha I, Ile-Alatau State National Nature Park, South-Eastern Kazakhstan.